INVESTIGATION OF THERMAL BEHAVIOR OF NIGELLAE SATIVAE SEMEN FROM DIFFERENT TYPES OF EXTRACTS - TOMA, Claudia-Crina; TITA, Bogdan; OLAH, Neli-Kinga; STATTI, Giancarlo Antonio (Studia Universitatis Babeș-Bolyai Chemia, 2018)
Thermal methods have an important applicability in the pharmaceutical field, such as raw material control, purity determination, thermal stability determination, substance compatibility, qualitative and quantitative analysis of drugs, etc. Data on substance stability are obtained from the analysis of thermal decomposition determinations that occur both under isothermal conditions and under non-isothermal conditions. Thermogravimetry and derived thermogravimetry (TG / DTG) and differential scanning calorimetry (DSC) that are used to study the compatibility of the active substances and excipients have become increasingly important, because identify possible interactions between these components of the drugs. These thermoanalytic techniques have been used to study the behavior of a Nigella sativa semen glycerin macerate. To obtain tinctures and glycerin macerates, the European Pharmacopoeia methodology was followed. The thermoanalytic curves were recorded in a dynamic atmosphere of nitrogen and air (20 ml / min). The sample heating rate was 10° C / min. Thermal TG / DTG and DSC methods were applied in the temperature range of 25-1000° C.